The antimicrobial efficacy of shielded ultraviolet germicidal irradiation in CT rooms with intense human circulation - Yıldırım, Gülşah (Diagn Interv Radiol, 2021)
PURPOSE: Computed tomography (CT) premises are one of the strategic points in the spread of hospital-acquired infections. Ultraviolet germicidal irradiation (UVGI) is an effective method that could potentially be used to purify the ambient air in them. However, it cannot be directly used in the presence of humans and, therefore, it is not operationally suitable in such units with continuous human circulation. Newer devices have been developed to purify air with more efficient and shielded UV-C sources. This study aims to assess the microbial air contamination in CT scanning rooms and investigates the efficacy and technical considerations of shielded UV-C arrays. METHODS: Two shielded UVGI systems, each equipped with 15 Watt UV-C LED arrays, were tested in a very busy CT unit. Initially, a pilot study was performed to determine ambient microorganisms under routine conditions before UVGI installation, followed by three basic scenarios of UVGI use under normal and abnormal conditions: A, UVGI, with both air-conditioning (AC) and ventilation on; B, UVGI, with AC on and ventilation off; C, UVGI, with both AC and ventilation off. Ambient air was sampled in various time points before and after the initialization of UV irradiation and analyzed for colony formation. RESULTS: The mean total colony count in the pilot study was 1360±450 CFU/m(3). Pre-UVGI colony count was 3510 CFU/m(3) for Scenario A, ~10000 CFU/m(3) for Scenario B and 990 CFU/m(3) for Scenario C. Thirty minutes after UVGI, total colony counts in all three scenarios dropped to 30 to 70 CFU/m(3). Under normal operating conditions and UVGI, the mean colony count was found as 21.4±13.5 CFU/m(3) and the average efficacy of the UVGI was found as 99.39%. CONCLUSION: This study identified substantial microbial air contamination in CT scanning rooms during normal and abnormal operating conditions. UV-C LED arrays effectively eliminate these microbiological contaminants. This effect is also observed under abnormal operating conditions where no other means of ventilation or air conditioning exists.